2008
DOI: 10.1200/jco.2006.10.4620
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Multicenter, Controlled Trial Comparing the Efficacy and Safety of Darbepoetin Alfa Administered Every 3 Weeks With or Without Intravenous Iron in Patients With Chemotherapy-Induced Anemia

Abstract: Addition of IV iron to darbepoetin alpha Q3W in patients with chemotherapy-induced anemia was well tolerated, resulting in an improved hematopoietic response rate and lower incidence of transfusions compared with darbepoetin alpha alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
160
3
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(193 citation statements)
references
References 27 publications
8
160
3
16
Order By: Relevance
“…Patients receiving IV iron had larger increases in hemoglobin levels, and hemoglobin response occurred earlier compared with patients not receiving IV iron. This is consistent with findings from other studies that have reported significant improvements in hemoglobin levels for patients receiving ESA therapy in combination with IV iron in the CIA setting [17][18][19][20][21]. In the present study, RBC transfusions were not different for the IV iron usage groups, consistent with findings from most studies evaluating iron usage in CIA patients [17,[19][20][21].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Patients receiving IV iron had larger increases in hemoglobin levels, and hemoglobin response occurred earlier compared with patients not receiving IV iron. This is consistent with findings from other studies that have reported significant improvements in hemoglobin levels for patients receiving ESA therapy in combination with IV iron in the CIA setting [17][18][19][20][21]. In the present study, RBC transfusions were not different for the IV iron usage groups, consistent with findings from most studies evaluating iron usage in CIA patients [17,[19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, RBC transfusions were not different for the IV iron usage groups, consistent with findings from most studies evaluating iron usage in CIA patients [17,[19][20][21]. Notably, the study by Bastit et al [18] showed a significant decrease in number of transfusions in the IV iron group compared with the no IV iron group. Inconsistent results were observed for achieving target hemoglobin and achieving hematopoietic response when data were stratified by baseline serum ferritin (<100 ng mL 21 vs. 100 ng mL 21 ), reinforcing the observation that serum ferritin is a poor predictor of response to IV iron, as show in previous studies [26].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations